NEAR DEATH EXPERIENCES AND THE DOCTRINE OF SUBTLE BODY - Sharma, Arvind (Journal of Dharma, 1979)
One of the books which has made considerable impact in the realm of transpersonal psychology in recent years is Life after Life by Raymond, A. Moody, Jr.,' which carries a foreword by that other great explorer of the experience of death, Elisabeth Kubler-Ross.s Since it was first published in November 1975, it has been condensed in the Reader's Digest" and has been cited in other articles recalling neardeath experiences.